Digestibility Of Maggot Black Soldier Fly (Hermetia Ilucens) Flour in Ration Of Kampong Chicken - Yunilas; Hasnudi; Naibaho, Geofani; Ginting, Nurzainah; Simanullang, Basta (Jurnal Peternakan Integratif, 2021)
Good quality animal feed was a determining factor for the success of livestock industry. Maggot BSF had the potential as a promising protein source feed. The aimed of this researceh was to investigate digestibility of crude protein, dry matter, organic matter of BSF maggot flour. The maggot was kept in media of fermented palm oil coir (FPOC) with dose of fermenter 1, 3, 5%. The maggot processed into flour and fed to kampong chickens. The reseach was conducted experimentally using a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were: M0 (fish meal), M1 (Maggot FPOC 1%), M2 (maggot FPOC 3%) and M3 (maggot FPOC 5%). Based on the results of the study, it was found that BSF had a significant effect (P <0.05) on protein digestibility (M0 = 75.70, M1 = 63.03, M2 = 73.32, and M3 = 56.24), a very significant effect (P <0.01) on the digestibility of dry matter (M0 = 64.72, M1 = 44.08, M2 = 44.26, and M3 = 37.43), and the digestibility of organic matter (M0 = 68.59, M1 = 45, 32, M2 = 48.08, and M3 = 47.47). Maggot flour from FPOC 3% produced good crude protein digestibility in kampong chicken compared to FPOC 1% and 3% .